How Can Both the Intervention and Its Evaluation Fulfill Health Promotion Principles? An Example From a Professional Development Program. Issue 4 (July 2013) - Tremblay, Marie-Claude; Richard, Lucie; Brousselle, Astrid; Beaudet, Nicole
The emergence over the past 20 years of health promotion discourse poses a specific challenge to public health professionals, who must come to terms with new roles and new intervention strategies. Professional development is, among other things, a lever for action to be emphasized in order to meet these challenges. To respond to the specific training needs of public health professionals, a team from the Direction de santé publique de Montréal (Montreal Public Health Department) in Quebec, Canada, established in 2009 the Health Promotion Laboratory, an innovative professional development project. An evaluative component, which supports the project's implementation by providing feedback, is also integrated into the project. This article seeks to demonstrate that it is possible to integrate the basic principles of health promotion into a professional development program and its evaluation. To this end, it presents an analytical reading of both the intervention and its evaluation component in light of the cardinal principles in this field. Initiatives such as the Health Promotion Laboratory and its evaluation are essential to consolidate the foundations of professional development and its assessment by concretely integrating health promotion discourse into these practices.